CareTrack Kids—part 2. Assessing the appropriateness of the healthcare delivered to Australian children: study protocol for a retrospective medical record review. Issue 4 (8th April 2015) - Hooper, Tamara D; Hibbert, Peter D; Mealing, Nicole; Wiles, Louise K; Jaffe, Adam; White, Les; Cowell, Christopher T; Harris, Mark F; Runciman, William B; Goldstein, Stan; Hallahan, Andrew R; Wakefield, John G; et al.
Abstract : Introduction: Australian and international clinical practice guidelines are available for common paediatric conditions. Yet there is evidence that there are substantial variations between the guidelines, recommendations (appropriate care) and the care delivered. This paper describes a study protocol to determine the appropriateness of the healthcare delivered to Australian children for 16 common paediatric conditions in acute and primary healthcare settings. Methods and analysis: A random sample of 6000–8000 medical records representing a cross-section of the Australian paediatric population will be reviewed for appropriateness of care against a set of indicators within three Australian states (New South Wales, Queensland and South Australia) using multistage, stratified sampling. Medical records of children aged <16 years who presented with at least one of the study conditions during 2012 and 2013 will be reviewed. Ethics and dissemination: Human Research Ethics Committee approvals have been received from the Sydney Children's Hospital Network, Children's Health Queensland Hospital and Health Service and Women's and Children's Hospital Network (South Australia). An application is under review for the Royal Australian College of General Practitioners. The authors will submit the results of the study to relevant journals and offer oral presentations to researchers, clinicians and policymakers at national and international conferences.